Preliminary Derived DInSAR Coseismic Displacements of the 2022 Mw 5.7 Stolac Earthquake - Antonio Banko; Fran Mihelin; Tedi Banković; Marko Pavasović (Remote Sensing, 2024)
On 22 April 2022, a Mw 5.7 earthquake was generated near Stolac (Bosnia and Herzegovina). The mainshock was succeeded by several aftershocks, three of which were significant. Two Mb 4.3 earthquakes occurred on 23 April 2022, and a Mw 4.8 earthquake was generated on 24 April 2022. Available data from fault mechanism solutions revealed that the mainshock activated a reverse fault, while the aftershock generated a normal fault with a right-lateral component. The Balkan Peninsula stands as one of the most active geodynamic areas in Central and Eastern Europe due to its location within the collision zone between Eurasian and African tectonic plates and the Anatolian microplate. Recorded earthquakes in Bosnia and Herzegovina are related to the energy generated by the subduction of the African tectonic plate under Eurasia. Furthermore, the seismicity of Bosnia and Herzegovina, particularly its southern part, is profoundly influenced by the subduction of the Adriatic microplate under the Dinarides. The Dinarides are a mainly fold and thrust belt that extends from the Southern Alps in the northwest to the Hellenides in the southeast and make dominant the tectonic system of Bosnia and Herzegovina. In this study, two pairs of SAR images obtained from the Sentinel-1 satellite mission were utilized to generate satellite LOS surface displacements using the DInSAR method. Moreover, LOS displacements were decomposed into vertical and east–west horizontal components by combining ascending and descending satellite orbits. Ultimately, the InSAR results were analyzed and compared with the data obtained from the CROPOS CORS GNSS station in Metković (MET3).